The Diagnostic Values of Ischemia-Modified Albumin in Patients with Acute Abdominal Pain and Its Role in Differentiating Acute Abdomen - Selman Yeniocak; Fatma Saraç; Mustafa Yazıcıoğlu; Nadiye Karabulut; Akın Ünal; Esma Yücetaş; Macit Koldaş; İbrahim Akkoç; Mustafa Ekici; Togay Evrin (Emergency Medicine International)
Aim. The aim of this study was to evaluate the diagnostic value of serum ischemia-modified albumin (IMA) levels in patients presenting to the emergency department with acute abdominal pain and its use in differentiating acute surgical abdomen. Methods. This single-center prospective cross-sectional study included 334 adult patients who presented to the emergency department. These consisted of 194 patients (Group 1) with nontraumatic abdominal pain commencing in the preceding week, who were definitely diagnosed and either hospitalized in a specific department or planned for discharge, and a control group of 140 patients (Group 2). Results. The mean IMA value of the patients diagnosed with acute appendicitis was statistically significantly higher than that of the control group. The mean IMA value of the patients diagnosed with acute appendicitis, ovarian pathologies, and gastritis-peptic ulcer was statistically significantly higher than that of the nonspecific abdominal pain group. Conclusion. Serum IMA levels can be used as a diagnostic marker in patients with acute appendicitis. Furthermore, serum IMA levels in patients presenting to the emergency department with abdominal pain may be indicative of patients requiring surgery or of complicated cases, particularly in terms of acute appendicitis and ovarian pathologies.